An Exploration of the Aesthetics of Dalit Trauma in Mulk Raj Anand’s "Untouchable" - Bianca Cherechés (Universitat Autònoma de Barcelona, 2019)
The Dalit community has suffered generational, multi-faceted and institutionalised discrimination as a result of the implementation of the Hindu caste system in the Indian society for religious and political reasons. This casteist practice has left a clear mark of social division and inequality and has severely damaged this community’s identity. Mulk Raj Anand, one of the pioneers in addressing this issue, offers a glimpse of what being a Dalit or untouchable entailed in pre-independent India in his short but intense novel Untouchable, in which he narrates episodes of verbal and physical violence and recurrent inter- and intra-caste discrimination, thus depicting the traumatic existence of this oppressed community. Therefore, the aim of this paper is to delineate the aesthetics of Dalit trauma as represented in this short novel and to determine the extent to which this model complies with the pre-existing paradigms of trauma theory or if they need to be reconsidered.